AB0221 ULTRASOUND ASSESSMENT OF INFLAMMATORY ARTHRALGIA: PREDICTORS FOR CHRONIC ARTHRITIS DEVELOPMENT. (13th June 2020) - Rodríguez-Merlos, P.; Peiteado, D.; Monjo, I.; Nuño, L.; Villalva, A.; Novella-Navarro, M.; Jenny Gabriella, T.; Miranda-Carus, M. E.; Fortea-Gordo, P.; De Miguel, E.; Balsa, A.
Abstract : Background: Inflammatory arthralgia (IA) onset is a common rheumatology consultation. Identifying predictors for chronic arthritis (CA) development by ultrasonography (US) may provide early diagnosis and treatment in order to prevent progression of the disease. Objectives: Establishing US findings that can be related to CA development in patients with inflammatory arthralgia without arthritis. Assess the link among US, clinical and biochemical parameters. Methods: A prospective longitudinal study of a cohort of patients with IA. Patients with less tan one year of AI evolution and involvement of at least one small joint from hands or feet were included. Patients with arthritis, osteoarthritis, fibromyalgia and those treated with DMARDs or steroids were excluded. We made a 6-monthly evaluation for 2 years and recorded the CA development during that period. The number of painful joints (PJC) and biochemical data (CRP, ESR) were assessed at the first visit. A blind US exploration was made using a MyLabTwice (Esaote) equipment with a 5-13MHz probe for greyscale (GS) and Power Doppler (PD), examining 36 joints (radio-carpals, MCP, IPP, 2nd-5th MTP, elbows, shoulders and knees) and 14 tendon compartments (2nd, 4th and 6th wrist extensors, 3rd and 4th finger flexors and posterior tibial and fibularis tendons), giving an overall score of GS, PD (0-3) and number of erosions by rating the presence of sinovitis on each location. We performed a descriptive analysis based on the frequencies of qualitative variables and mean±SD/median (IQR) of quantitative variables, comparing the characteristics between patients with and without CA progression by Chi-Square and Mann-Whitney U tests. Also, the possible relationship of those variables and the disease progression was assessed by a univariate binary logistic regression analysis. We designed a reduced US examination (RUE) selecting the most affected locations and those with greatest differencies between groups in the statistical analysis. Results: Of the 49 patients included, 21 (42.9%) progressed to CA. 87% were females and 71.4% non-smokers with a mean age of 44 ± 12 years. The median of PJC was 4 (1-9). RF and/or CCPA were positive in 18.4% and 34.7% had high CRP/ESR. The suggested RUE included carpi, 2nd-4th MCP, 2nd-3rd IPP, 2nd and 5th MTP, 4th and 6th wrist extensors and fibularis tendons. Scores and comparative analysis within subgroups are listed in Table 1 . The RUE score was significantly greater in both GS (OR 1.4, CI 95%) and PD (OR 1.3, CI 95%) on patients that progressed to CA. There were no significant associations between RF/CCPA positivity or CRP/ERS levels and US findings. Conclusion: Patients with IA without arthritis that progressed to CA had significant higher GS and PD scores, hence showing the utility of US to predict disease progression. A RUE of 8 joints and 3 tendon compartments could be enough to achieve this goal. Disclosure of Interests: Pablo Rodríguez-Merlos: None declared, Diana Peiteado: None declared, Irene Monjo: None declared, Laura Nuño: None declared, Alejandro Villalva: None declared, Marta Novella-Navarro: None declared, Torres Jenny Gabriella: None declared, Maria-Eugenia Miranda-Carus Grant/research support from: BMS, Roche, Paula Fortea-Gordo Grant/research support from: BMS, Eugenio de Miguel Grant/research support from: Yes (Abbvie, Novartis, Pfizer), Consultant of: Yes (Abbvie, Novartis, Pfizer), Paid instructor for: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi), Speakers bureau: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi), Alejandro Balsa Grant/research support from: BMS, Roche, Consultant of: AbbVie, Gilead, Lilly, Pfizer, UCB, Sanofi, Sandoz, Speakers bureau: AbbVie, Lilly, Sanofi, Novartis, Pfizer, UCB, Roche, Nordic, Sandoz